Antioxidant capacity and concentration of redox-active trace mineral in fully weaned intra-uterine growth retardation piglets. Issue 1 (December 2015) - Zhang, Hao; Li, Yue; Wang, Tian
Abstract Background The redox status of intra-uterine growth retardation (IUGR) piglets post-weaning has been poorly studied. Methods Newborns from twenty-four sows were weighted, weaned at 21 d and fed a starter diet until sampling. Sampling was done at 14 d post-weaning. A piglet was defined as IUGR when its birth weight was 2 SD below the mean birth weight of the total population. At weaning, eighteen piglets with nearly equal body weight from each category (i.e. IUGR or normal birth weight (NBW) piglets) were selected and then allocated to two treatments, consisted of six replicates with each pen having three piglets. Results Compared with NBW group, IUGR significantly decreased average daily gain (P  < 0.001), average daily feed intake (P  = 0.003), and feed efficiency (P  < 0.001) of piglets during the first two weeks post-weaning. IUGR decreased the activities of total antioxidant capacity (P  = 0.019), total superoxide dismutase (T-SOD, P  = 0.023), and ceruloplasmin (P  = 0.044) but increased the levels of malondialdehyde (P  = 0.040) and protein carbonyl (P  = 0.010) in plasma. Similarly, the decreased activities of T-SOD (P  = 0.005), copper- and zinc-containing superoxide dismutase (Cu/Zn-SOD, P  = 0.002), and catalase (P  = 0.049) was observed in the liver of IUGR piglets than these of NBW piglets. IUGR decreased hepatic Cu/Zn-SOD activity (P  = 0.023) per unit of Cu/Zn-SOD protein in piglets when compared with NBW piglets. In addition, IUGR piglets exhibited the decreases in accumulation of copper in both plasma (P  = 0.001) and liver (P  = 0.014), as well as the concentrations of iron (P  = 0.002) and zinc (P  = 0.048) in liver. Compared with NBW, IUGR down-regulated mRNA expression of Cu/Zn-SOD (P  = 0.021) in the liver of piglets. Conclusions The results indicated that IUGR impaired antioxidant capacity and resulted in oxidative damage in fully weaned piglets, which might be associated with the decreased levels of redox-active trace minerals. This study highlights the importance of redox status in IUGR offspring and provides a rationale for alleviating oxidative damage by dietary interventions aiming to supplement trace minerals and to restore redox balance in the future.